Community Perception and processes of Integrated Coastal Zone Management in the North Pacific of Costa Rica. - Sánchez-Jiménez, Astrid (2014)
The tendencies in perception on use and management of marine and coastal resources in the North Pacific of Costa Rica were studied through consultation workshops in the communities of Cuajiniquil, Villarreal, Montezuma, and surrounding areas. A total of 112 people from eight communities attended the workshops. Overall, there was higher attendance by men than by women. The main marine resources identified were fisheries and beach/waves; highlighted activities were fishing and tourism. The Costa Rican Institute of Fishing and Aquaculture (Incopesca) was identified as having deficient participation in the management of resources, besides was assigned low participation to the artisanal fishing and tourism. The involvement of women as leaders in Montezuma was highlighted, which emphasized the need to promote the autonomy of coastal women so that more female citizens are in the condition to contribute as legitimate stakeholders in the decision making process. The main challenges detected were illegal fishing in Marine Protected Areas and overfishing. As solutions, the communities proposed elements of sustainable fishing, and the elimination of trawling and compressor diving. The consultation process revealed the need to propose economic alternatives to fishing, the education of local communities, focus more attention on management categories that do not prohibit artisanal fishing, and to promote the participation of the civil society in the decision making process. Existing mechanisms should be used to promote community inclusion and participatory processes. Rev. Biol. Trop. 62 (Suppl. 4): 139-149. Epub 2014 Diciembre 01.